La seguridad jurídica, legalidad y tipicidad en el derecho administrativo sancionador del libro I del COESCOP. - Sandoval, Walter M. (2022)
As a constitutional perspective, the guarantees are the support of legal security that a “person” has against the State as ways and procedures to ensure the validity of rights; which, along with some principles, such as legality and typicity become suitable tools for the right utilization of regulations in any field. The objective of this research was to evaluate whether the disciplinary administrative law for the National Police prescribed in the Book I of the COESCOP (2017) meets the requirements of legal security prescribed in the CRE (2008) and the postulates of the principles of legality and typicality offered by legislation, doctrine and jurisprudence. Through a methodology based on a qualitative approach and a critical analytical method, the content of the COESCOP disciplinary regime was analyzed and after a documentary, descriptive and evaluative investigation of the sources of police disciplinary law, it was determined that the content of some administrative offenses disciplinary measures does not comply with the requirements and parameters ordered by the Magna Carta. Analyzing the foundations of the restrictive and flexible vision regarding typicity and developed by classical and contemporary doctrine and jurisprudence, respectively, it was concluded that it is necessary to lean towards the first one in order to guarantee the right to legal certainty, since when applying the flexibility of this principle runs the risk of generating arbitrary procedures based on subjective interpretations, as has been evidenced in the cases presented.